Glycemic control and the risk of tuberculosis in patients with diabetes: A cohort study in a Mediterranean city - Antonio-Arques, Violeta; Caylà, Joan A.; Real, Jordi; Moreno-Martinez, Antonio; Orcau, Àngels; Mauricio, Didac; Mata-Cases, Manel; Julve, Josep; Navas Mendez, Elena; Puig Treserra, Rai; Millet, Joan Pau; Del Val García, Jose Luis; et al. (Frontiers in Public Health, 2022)
Background. Diabetes mellitus (DM) is one of the leading chronic diseases globally and one of the most common causes of death, morbidity, and poor quality of life. According to the WHO, DM is also one of the main risk factors for developing active tuberculosis (TB). Subjects with DM are at a higher risk of infections, in addition to frequent micro- and macrovascular complications, and therefore sought to determine whether optimized glycemic control lowered the risk and severity of TB. Methods. We used a retrospective cohort of diabetic subjects to predict the incidence of TB. All diabetic patients were recruited from Ciutat Vella (the inner-city district of Barcelona) from January 2007 until December 2016, with a follow-up period until December 2018 (≥ 2 years). Data were extracted from Barcelona's Primary Care medical record database - SIDIAP, linked to the Barcelona TB Prevention and Control Program. The incidence of TB and the impact of glycemic control were estimated using time-to-event curves analyzed by Cox proportional hazard regression. Hazard ratios (HRs) and 95% confidence intervals (CIs), unadjusted and adjusted by potential confounding variables, were also assessed, which included age, sex, diabetes duration, macrovascular and microvascular signs, BMI, smoking habit, and alcohol consumption. Results. Of 8,054 DM patients considered for the study (equating to 68,605 person-years for follow-up), 84 developed TB (incident rate=70 [95% CI: 52-93] per 100,000 person-years). Diabetic subjects with TB were younger (mean: 52.2 vs. 57.7 years old), had higher values of glycosylated hemoglobin (HbA1c) (7.66% vs. 7.41%) and total triglycerides (122 vs. 105 mg/dl), and had twice the frequency of diabetic nephropathy (2.08% vs. 1.18%). The calculated incidence rate increased with increasing HbA1c: 120.5 (95% CI 77.2-179.3) for HbA1c 7.5%, 143 (95% CI 88.3-218.1) for HbA1c8%) and 183.8 (95% CI 105-298) for HbA1c ≥9%. An increase in the risk of TB was also observed according to a poorer optimization of glycemic control: adjusted HR 1.96 (95% CI 0.69-5.58), 2.23 (95% CI 0.76-6,54), and 3.06 (95% CI 1.07-8.78), respectively. Conclusion. Diabetic subjects with worse glycemic control, especially those with HbA1C ≥9%, were more at risk of developing TB.